Analyzing the Driving Components in the Successful Implementation of Improvement and Renovation of Rural Housing Projects Case: Khodabandeh - jafar yagobei; abolfazl rangvar; zahra khoshnodifar (جغرافیا و توسعه, 2013)
Nowadays, awareness of the facilities and problems of rural areas and analyzing them is very important in the process of rural development planning and considered necessary to provide some kind of plans and development programs. Rural improvement projects are rural development projects in which it is tried to improve  and organize rural housing. The purpose of this study was to analyze driving components in successful implementation of improvement and reconstruction plans in rural housing.  A descriptive–correlation survey approach was used in this study. The statistical population of this study consisted of the rural housing loan recipients in 2009 in Khodabandeh, Zanjan province. Sample size was estimated using Cochrane formula (n=1040) and selected with random sampling method. . The questionnaire was used for data collection in this study. Reliability and content validity has been confirmed using Cronbach's coefficient alpha (0.80), and surveys of specialists and professors associated with the issue. Data analysis has been made by using SPSS software. Results of factor analysis has shown that technical(20.82), service - credit(18.74), social - cultural (12.35) and organizational – administrative(11.56) are most important factors driving the successful implementation of improvement and renovation projects of rural housing that has explained 63.48 percent of total variance.